Reflections on methodology and interdisciplinarity in the postmodern dialogue between theology and the natural sciences - M. C. de Lange (Acta Theologica)
Postmodern interdisciplinarity provides a more flexible and productive methodological framework for the age-old dialogue between theology and the natural sciences than did the modern more rigid and oppositional disciplinary framework. Taking the work of Wentzel van Huyssteen as basis, the author focuses on developing an understanding of the roles of interdisciplinarity, foundationalism, non-foundationalism, and postfoundationalism in the dialogue between theology and science, and highlights the methodological changes resulting from the change-over from modernity to postmodernity.